AKTIVITAS ANTIFUNGI EKSTRAK DAUN KEMANGI (Ocimum americanum L.) TERHADAP FUNGI Fusarium oxysporum Schlecht - Zainal Berlian; Fitratul Aini; Weni Lestari (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2016)
Fusarium oxysporum Schlecht. a parasitic fungus that cause leaf wilt disease in plants. Meanwhile, basil (Ocimum americanum L.) is a plant that contains of the active compound in the form of phenols which have antifungal activity. This study aimed to test whether the extract of leaves of basil have antifungal activity againts Fusarium oxysporum Schlecht. and determine the optimum concentration to inhibit the growth of the fungus Fusarium oxysporum Schlecht. Antifungal test is done by using paper disc diffusion method. The study design used was a completely randomized design with 4 treatments and 6 replications. The treatment is K0 (0% w/v), K1 (5% w/v), K2 (10% w/v), and K3 (15% w/v). The results showed that the leaf extract of basil have antifungal activity against Fusarium oxysporum Schlecht. Inhibition zone on K0, K1, K2, and K3 are each 0,0 mm, 1,49 mm, 2,46 mm, and 2,01 mm. The optimum concentration of antifungal activity of extract of basil, namely the K2 concentration (10% w/v). Based on analysis of variance (ANOVA), the concentration of basil leaf extract provides significant differences (p > 0,05) on fungus Fusarium oxysporum Schlecht., where Fcount > Ftable is 4,5 > 3,1.